EPISTOLARY SOURCES ON HISTORY IMAMAT: CORRESPONDENCE OF DANIYAL-BEK OF ELISU - Abdulmazidov, Ramazan Sultanovic; Magomedova, Zejnab Ahmeddibirovna (History, Archeology and Ethnography of the Caucasus, 2018)
The Collection of Oriental manuscripts of the Institute of History, Archaeology and Ethnography of the Daghestan scientific center of the Russian Academy of Sciences contains extensive correspondence of Daniyal-Bek - a famous associate of Imam Shamil, including not yet introduced into scientific circulation. This hereditary aristocrat, the representative of one of the most influential Daghestan feudal clans has played a significant role in the people's liberation movement of mountaineers of Daghestan and Chechnya under the leadership of imam Shamil. The pride temper and Daniyal-bek's ambitions have led to the conflict with one of commanders of imperial army then he has passed into the Caucasian imamat. In the present work documents related with his activity as a naib and mudir of Shamil are published. In this article, the authors give their full translation, which is provided with detailed comments. Published documents, a total of 27 letters, most of which are originals, are given in compliance with the chronological sequence. They are preceded by an interesting memorable record of the fate of Daniyal-Bek, made, in our opinion, by Mukhammadtakhir al-Karakhi, the translation of which we considered necessary to include in this work. Daniyal-bek's correspondence allows to gain an impression about duties of naib on providing troops with necessary provisions and ammunition, about various lawsuits, imposing of penalties and punishments, about decision-making according to civil suits, questions of trade, investigation, etc. Recipients and senders of letters to Daniyal-Sultan act as the highest leadership of the Caucasian Imamat in the person of Shamil and Sheikh Djamaluddin, and naibs, qadis, centurions and scouts. The publication of the correspondence will significantly fill the gaps in coverage of the activities of this famous naib and mudir.
Keywords: Daghestan; Caucasian War; Daniyal-Sultan; Daniyal-Bek of Elisu; Imamate; Shamil; correspondence